Program Dinas Pemberdayaan Masyarakat Dan Desa Dalam Memajukan Perekonomian Desa Leubatang Di Kecamatan Omesuri Kabupaten Lembata Nusa Tenggara Timur - Siti Risdayanti Muslimin; St. Nasriah (Universitas Islam Negeri Alauddin Makassar, 2024)
This thesis discusses the Community and Village Empowerment Service Program in Advancing the Economy of Leubatang Village in Omesuri District, Lembata Regency, East Nusa Tenggara. Furthermore, the researcher elaborated into two sub-problems, namely: 1). What is the Program of the Community and Village Empowerment Office in Advancing the Economy of Leubatang Village in Omesuri District, Lembata Regency, East Nusa Tenggara? 2). What are the Inhibiting and Supporting Factors in the Implementation of the Program to Advance the Economy of Leubatang Village in Omesuri District, Lembata Regency, East Nusa Tenggara?.This type of research is qualitative descriptive which is carried out by studying in depth a problem and then the results are described. The approach method used in this study is a sociological approach. The data collection method consists of observation, interviews and documentation. Data processing techniques consist of data analysis, data reduction, and data presentation. Furthermore, the last research method used by the researcher is to draw conclusions.The results of this study show that: (1) The Program of the Community and Village Empowerment Office in Advancing the Economy of Leubatang Village in Omesuri District, Lembata Regency, East Nusa Tenggara, namely the Mutiara Village-Owned Enterprise (BumDes) called